The significance of transcervical ultrasound-guided radiofrequency ablation in the treatment of symptomatic fibroids: results of an expert consensus from German-speaking countries - Roemer, Thomas; Bends, Ralf; Christoffel, Ladina; Felberbaum, Ricardo; Hildebrandt, Thomas; Meinhold-Heerlein, Ivo; Mueller, Michael; Oppelt, Peter; Renner, Stefan P.; Runnebaum, Ingo B.; Schiermeier, Sven; Piriyev, Elvin; et al. (Archives of Gynecology and Obstetrics, 2022)
Uterine fibroids are one of the most common diseases in female patients, lead mainly to bleeding disorders and lower abdominal pain, and reduce the chance of having children. In recent years we have seen a trend towards more and more pharmacotherapies and minimally invasive organ-preserving treatments. One novel and innovative procedure for an organ-preserving treatment of symptomatic uterine fibroids is the transcervical ultrasound-guided radiofrequency ablation (TRFA). TRFA has been used in Germany since 2013 and later found use in other German-speaking countries as well. There have now been more than 1200 TRFA treatments performed in Germany, Austria, and Switzerland. Experts from these three countries came together for a consensus meeting to analyze the significance of the procedure in the overall concept of the treatment of symptomatic uterine fibroids.
CRIS-Team WoS Importer:2022-04-01